Sistem Informasi Pendaftaran untuk Kompetisi Airsoft Group dengan Metode Prototyping - Rahmat Bastian, Deka; Widyanto, R.Arri; Pujiarto, Bambang (Universitas Muhammadiyah Magelang, 2019)
The Airsoft Group Competition (ARGO) is an airsoft gun championship event held after the airsoft fan group Anarchy99 Magelang. The manual registration system in airsoft competition has many disadvantages, it requires time to search for participant data, it is prone to double participants that are not needed by the competition participants and if there are participants with the same name, it is difficult for one participant to another. The purpose of this study is to obtain a registration information system to facilitate participants and organizers in carrying out the registration process and making reports. With a large number of participants spread throughout Indonesia, this championship requires information systems. The method used in making this information system uses the prototype method. The results obtained from research testing with the Black Box Testing method and conducted on the user, can be concluded related to the system built has met the needs of the procurement of information systems that help the registration process and help the participant data and conduct purchase. Requires a long time in making reports.